Spitz Tumors: Comparison of Histological Features in Relationship to Immunohistochemical Staining for ALK and NTRK1. (May 2016) - Kiuru, Maija; Jungbluth, Achim; Kutzner, Heinz; Wiesner, Thomas; Busam, Klaus J.
Spitz tumors are a group of melanocytic neoplasms with distinct morphological features that tend to affect young individuals. Distinguishing benign from malignant Spitz tumors can be challenging, but cytogenetic and molecular tests have contributed to improvements in diagnostic accuracy. Spitz tumors harbor diverse genetic alterations, including mutations in HRAS, loss of BAP1, or kinase fusions in ROS1, NTRK1, ALK, BRAF, and RET genes. Limited data exist on the correlation between histopathological features and kinase fusions. Here, we describe the histopathological features of 105 Spitz tumors (Spitz nevi and atypical Spitz tumors), comparing lesions according to their immunoreactivity for ALK or NTRK1. Intersecting fascicular growth of fusiform melanocytes was seen in all but one ALK-positive tumor (27 of 28 or 96.4%), whereas it was infrequent in NTRK1-positive tumors (5 of 20 or 25.0%) and tumors negative for both ALK and NTRK1 (96.4% vs 25.0% vs 8.7%, P < .0027). There was a trend toward ALK-positive tumors being amelanotic compared with NTRK1-positive tumors and combined ALK-/NTRK1-negative tumors (89.3% vs 45% vs 47.4%, respectively, P = .1023) and lacking epithelioid cell morphology (0% vs 45.0% vs 41%, respectively, P = .6985). In conclusion, this study confirms that although not specific, the growth pattern of intersecting fascicles of amelanotic fusiform melanocytes is strongly associated with ALK expression.